Níveis críticos de fósforo para o crescimento do estilosantes como função do fator capacidade de fósforo no solo - Morel Freire , Francisco; Ferreira de Novais , Roberto; Lima Neves , Júlio Cesar (Revista Ceres, 2025)
An experiment was conducted in the greenhouse to study the effect of levels of P on the growth of stylosantes cv. ‘IRI 1022’ cultivated on ten Latosol samples with large textural variation. Previously, the soil samples received 0, 30, 90, 270 and 540 kg/ha of P as NaH2PO4.Hy0, and were planted to soybean, eucaliptus and rice.